PERENCANAAN PENJADWALAN DAN PERSEDIAAN SPAREPART DENGAN METODE RELIABILITY CENTERED MAINTENANCE (RCM) DI PT.X - Evi Siswanti (JURNAL TEKNIK INDUSTRI, 2016)
PT.X is a supplier company that manufactures plastic bottles. Currently PT.X has aproduction capacity of 4.3 million bottles per day. The production capacity can be met if theproduction machine running well and in a reliable state. PT.X not currently have a machinemaintenance activities are laid out well. This often caused many damage occurs unscheduledengine which causes the cost of lost opportunity (opportunity cost) for the manufacture ofproducts and the high costs of component inventory. The method used in solving the problem inthis study is the use of Reliability Centered Maintenance analysis in determining the policy oftreatment and then seek maintenance intervals based on the minimum cost. The results obtainedare contained 8 components that have critical categories with each scheduled maintenance policyis age replacement, with this calculation obtained a saving of approximately 44% on inventorycosts and increased reliability component approximately 42% -64%.